An implementation of digital technologies to improve productivity and reduce non-value adding activities in the production process - Marija Stanojeska (University American College Skopje, 2022)
In today's smart manufacturing environment, the textile industry faces challenges such as efficiency, sustainability, and a quick response to clients' dynamic requirements as well as productivity that can ensure its survival. Production has been influenced due to a lack of technological advancement, leading to a negative effect on overall performance. Although the relevance of the use of information and communications technology tools to design more reliable and improved processes is still an unexplored area. The aim of the study is to present the benefits of using software-oriented tools in the textile industry, as one of the most vulnerable types of industries. Namely, the research was conducted in a textile factory in which an intelligent platform was installed for gathering, measuring, and processing data in real-time in terms of the productivity of the manufacturing process. For the purpose of this research, the methodology of collecting, analyzing, and comparing data was implemented. The findings indicate that the implementation of appropriate digital technologies allows the reduction of non-value adding activities and the improvement of the overall productivity of the production process. In addition, this smart platform will serve as a technology benchmark and a roadmap for other textile factories, especially in emerging economy countries.
Keywords: 330; Digital technologies; Software-based tools; Non-value adding activities; Productivity; and Production process